Screening And Characterisation Of Inhibitors For Glyoxylate Cycle ICL Enzyme Activity In Candida Albicans - Cheah, Hong Leong (2014)
Candida albicans is an opportunistic pathogen that causes candidiasis in human. Metabolic pathways have been recently explored as potential antimicrobial targets, for example glyoxylate cycle that enables the C. albicans to servive nutrient-limited niches. Glyoxylate cycle and its key enzymes would be an attractive antifungal drug target for C. albicans. In this study, an alternative cell-based screening approach that better reflect the physiological environment in host system was employed to identify lead compounds that inhibit the glyoxylate cycle.